2011
DOI: 10.1186/1471-2334-11-219
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in Sudan: a study of Mycobacterium tuberculosis strain genotype and susceptibility to anti-tuberculosis drugs

Abstract: BackgroundSudan is a large country with a diverse population and history of civil conflict. Poverty levels are high with a gross national income per capita of less than two thousand dollars. The country has a high burden of tuberculosis (TB) with an estimated 50,000 incident cases during 2009, when the estimated prevalence was 209 cases per 100,000 of the population. Few studies have been undertaken on TB in Sudan and the prevalence of drug resistant disease is not known.MethodsIn this study Mycobacterium tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 15 publications
7
42
2
Order By: Relevance
“…In the present study, the proportion of rifampicin-resistant M. tuberculosis was significantly higher among previously treated patients compared to treatment naive patients which might be due to failure from previous treatment and contact with drug resistant TB patients [26, 38–43]. However, the level of rifampicin resistance among previously untreated cases (6.7%) in the analysis close to the reported prevalence of rifampicin- resistant MTB (10.4%).…”
Section: Discussionsupporting
confidence: 68%
“…In the present study, the proportion of rifampicin-resistant M. tuberculosis was significantly higher among previously treated patients compared to treatment naive patients which might be due to failure from previous treatment and contact with drug resistant TB patients [26, 38–43]. However, the level of rifampicin resistance among previously untreated cases (6.7%) in the analysis close to the reported prevalence of rifampicin- resistant MTB (10.4%).…”
Section: Discussionsupporting
confidence: 68%
“…Another study from Ethiopia reported 38.9% CAS strains (8), and CAS/Delhi was the predominant lineage in a study from Sudan (32). CAS/Delhi strains have been circulating in Central Asia, the Middle East, Saudi Arabia (33) and India (34) for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacteria laboratory facilities in Sudan exist only in Khartoum state whereas TB patients from other states are referred to Khartoum state for diagnosis and treatment. The MDR-TB prevalence in Sudan was found in 5% of new cases and 24% of previously treated patients [3]. Recent development of the Xpert MTB/RIF test [4] and of the line probe assay [5] which span 81-bp fragment of the RNA polymerase beta subunit (rpoB) gene have allowed for the rapid detection of resistance to rifampicin (RIF).…”
Section: Multidrug-resistantmentioning
confidence: 99%